Cognitive and Psychological Sequelae of COVID-19: Age Differences in Facing the Pandemic - Devita, Maria; Di Rosa, Elisa; Iannizzi, Pamela; Bianconi, Sara; Contin, Sara A.; Tiriolo, Simona; Bernardinello, Nicol; Cocconcelli, Elisabetta; Balestro, Elisabetta; Cattelan, Annamaria; Leoni, Davide; Mapelli, Daniela; et al. (Frontiers in Psychiatry, 2021)
Literature about Covid-19 is currently focusing on the potential cognitive and neuropsychiatric sequelae observed in individuals receiving Intensive Care Unit (ICU) treatments. The aim of the present study is to evaluate the differences in cognitive and psychological sequelae of Covid-19 between younger and older adults, regardless of being or not in ICUs. The study involved 299 individuals (from 18 to 90 years old), who underwent a comprehensive cognitive and psychological assessment. Linear regression models were conducted separately for MoCA and PCL scores to investigate on them the effect of socio-demographic and clinical characteristics. Separate linear regression models were then applied sorting participants by age: younger adults (<65 years) and older adults ( 65 years). In the whole sample PCL scores were predicted by the intensity of care received, by being intubated, and by the persistence of cough after one month after hospitalization. Only age had instead an effect on cognition. In younger adults PCL scores were predicted by the presence of neurological symptoms, by the intensity of care received, and by being intubated; MoCA scores were only predicted by the intensity of care received. No significant associations were found in older adults. Psychological negative effects of Covid-19 pandemic particularly affect under-65 years old individuals, who also subjectively report cognitive sequelae associated with the infection. Over-65 years old individuals, instead, seem to be free from psychological and cognitive difficulties due to Covid-19.